Serious Hazards of Transfusion (SHOT) haemovigilance and progress is improving transfusion safety - Bolton-Maggs, Paula H B (John Wiley & Sons, 2013)
The Serious Hazards of Transfusion (SHOT) UK confidential haemovigilance reporting scheme began in 1996. Over the 16 years of reporting, the evidence gathered has prompted changes in transfusion practice from the selection and management of donors to changes in hospital practice, particularly better education and training. However, half or more reports relate to errors in the transfusion process despite the introduction of several measures to improve practice. Transfusion in the UK is very safe: 2·9 million components were issued in 2012, and very few deaths are related to transfusion. The risk of death from transfusion as estimated from SHOT data in 2012 is 1 in 322 580 components issued and for major morbidity, 1 in 21 413 components issued; the risk of transfusion-transmitted infection is much lower. Acute transfusion reactions and transfusion-associated circulatory overload carry the highest risk for morbidity and death. The high rate of participation in SHOT by National Health Service organizations, 99·5%, is encouraging. Despite the very useful information gained about transfusion reactions, the main risks remain human factors. The recommendations on reduction of errors through a ‘back to basics’ approach from the first annual SHOT report remain absolutely relevant today.